Selenium action in neuro-oncology - Yakubov, Eduard; Buchfelder, Michael; Eyupoglu, Ilker Y.; Savaskan, Nic E. (Biological trace element research, 2014)
The trace element selenium and selenocysteine-carrying selenoproteins play a pivotal role in the brain. Beside the essential function during development and maintenance of brain action, selenium has also been associated with several neurological and neuro-oncological conditions. Reliable supply of selenium is important since selenium compounds can affect tumor microenvironment and neoangiogenesis in malignant gliomas (WHO grade III and IV [glioblastoma, GBM]) via induction of apoptosis and alteration of matrix metalloproteinases expression. Here, we summarize recent findings focusing on the anti-toxicity and cancer-preventive properties of selenium and their implication in current multimodal therapies including temozolomide (Temodal), cyclophosphamide (Endoxan), and cisplatin (DDP, Platiblastin, and Platinol). We shed light on unintended side effects in chemotherapy and the developments of novel combinatorial chemotherapeutics with selenium compounds. We found that selenium and selenium compounds have dual action profiles with direct anti-cancer and chemotherapy-intensifier effects as well as neuroprotective and cytoprotective agents. Current selenium trials and selenium supplementation with focus on neuro-oncology will be discussed with regard to low-adequate-to-high/toxic selenium status.
EVALuna2:22848